2020
DOI: 10.1080/19490976.2020.1805281
|View full text |Cite
|
Sign up to set email alerts
|

Gut commensal microbiota and decreased risk for Enterobacteriaceae bacteriuria and urinary tract infection

Abstract: Urinary tract infection (UTI) is a common complication in kidney transplant recipients and can lead to significant morbidity and mortality. Recent evidence supports a role for the gut as a source for UTIs but little is known about the relationship between gut commensal bacteria and UTI development. We hypothesized that the abundance of gut commensal bacteria is associated with a lower risk of developing bacteriuria and UTIs. We performed gut microbiome profiling using 16S rRNA gene sequencing of the V4-V5 hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 29 publications
4
27
0
2
Order By: Relevance
“…In our study, Romboutsia was identified as a robust and strong biomarker in the relation between Met-T2D and the gut microbiome in both ethnicities. Besides its potential relation to metformin use [24,61,62], Romboutsia was also previously negatively correlated with the abundance of Enterobacteriaceae, in line with the observed higher abundance of Escherichia/Shigella in Met-T2D cases in our study [63]. As for the other overlapping ASVs, the effect of Met-T2D remained significant on the abundance of Clostridium sensu stricto 1, Peptostreptococcaceae Terrisporobacter and Intestinibacter bartlettii, and Escherichia/Shigella after all adjustments in African Surinamese, while those significant effects vanished in South-Asian Surinamese after adjustment for other medication use (often not addressed in the previous studies).…”
Section: Overlapping Biomarkers Between Ethnicities Were Previously Related To Metformin Usesupporting
confidence: 89%
“…In our study, Romboutsia was identified as a robust and strong biomarker in the relation between Met-T2D and the gut microbiome in both ethnicities. Besides its potential relation to metformin use [24,61,62], Romboutsia was also previously negatively correlated with the abundance of Enterobacteriaceae, in line with the observed higher abundance of Escherichia/Shigella in Met-T2D cases in our study [63]. As for the other overlapping ASVs, the effect of Met-T2D remained significant on the abundance of Clostridium sensu stricto 1, Peptostreptococcaceae Terrisporobacter and Intestinibacter bartlettii, and Escherichia/Shigella after all adjustments in African Surinamese, while those significant effects vanished in South-Asian Surinamese after adjustment for other medication use (often not addressed in the previous studies).…”
Section: Overlapping Biomarkers Between Ethnicities Were Previously Related To Metformin Usesupporting
confidence: 89%
“…Finally, a study by Magruder et al from 2020 demonstrated that high relative abundances of two bacterial taxa— Faecalibacterium and Romboutsia —can be linked to the decreased risk for Enterobacteriaceae bacteriuria and UTI in kidney transplant recipients [ 40 ]. This research group additionally reported an inverse relationship of the relative abundances of the aforementioned two taxa with the relative abundance of Enterobacteriaceae , lending further support for a growing notion that intestinal commensal organisms are related with lower risk of infectious complications, which is already deep-rooted for Clostridioides difficile infections [ 40 ].…”
Section: The Importance Of Gut Microbiota In Urinary Tract Infectimentioning
confidence: 99%
“…For the genera enriched in healthy controls, Anaerostipes , Gemella , and Parvimonas were reported to be scarce and primarily enriched in the healthy gut ( Bodkhe et al, 2019 ; Hong et al, 2019 ; Magruder et al, 2020 ). Clostridium XVIII/XlVa/XlVb, Fusobacterium , and Romboutsia are all major SCFAs, particularly butyrate producers in the process of human metabolism ( Duncan et al, 2002 ; Bui et al, 2014 ; Neijat et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%